Hooker Electrochemical Company after Twenty-Five Years, Manufacturers of High Grade Chemicals - Hooker Chemical Corporation (Hooker Chemical Corporation, 1929)
Publication providing a thorough corporate history of the Hooker Electrochemical Company, an American chemical company that produced chloralkali products from 1903 until 1968 when it was acquired by Occidental Petroleum. Between 1943 and 1953, Hooker disposed of chemical waste from its Niagara Falls plant in Love Canal, New York, leading to a harmful environmental disaster in the 1970s. This work includes chapters detailing the manufacture, use, and physical characteristics of the company's products including Caustic Soda, Chlorine, and Benzoic Acid. Work is thoroughly illustrated and digitized in its entirety.
Keywords: Chemical industry; Corporations; Electrochemicals industry; Electrochemistry, Industrial; Electrochemistry; Hooker Chemical Corporation